Effectiveness of the Integrated Service and Referral System in Handling Social Welfare Problems of the Poor - Rizkiya Sriwahyuni; Tuah Nur; Yana Fajar FY Basori (Program Pascasarjana Universitas Negeri Makassar, 2023)
The Sukabumi City Integrated Referral Service System (SLRT) is a program implemented in 2013 to help identify the poor and vulnerable to poverty. Providing information on various social protection and poverty reduction programs to the community. The purpose of this research is to find out how effective the Integrated Service and Referral System is in handling the social welfare problems of the poor in Sukabumi City. This research uses Campbell's theory. This research method uses qualitative methods. Data collection techniques were observation, interviewing, and documentation. Data validation methods used technical triangulation and source triangulation. The data analysis used was from Miles and Huberman, with data reduction, data presentation, and conclusion drawing. The results of this study indicate that the SLRT has been running in accordance with the stipulated law; its implementation has been quite effective in reducing poverty, but outreach to all the people of Sukabumi City is still uneven, and the socialization carried out is still lacking, both offline and online using social media, so that many people are not aware of the SLRT. The SLRT must improve its implementation in accordance with the SLRT General Implementation Guidelines No. 25 of 2017 so that it is more effective.